Power system modeling and simulation with energy storage system - Li, Shan (Nanyang Technological University, 2023)
Maintaining power system frequency stability is crucial as grid-connected wind power capacity continues to grow. The wind power generation fluctuations can cause the power imbalance in power systems, thereby deteriorating the frequency quality and threatening power system security. The time-domain simulation is an efficient way of studying system dynamics and assessing security. In this report, the negative impact of wind power penetration and fluctuations on power system frequency security is validated by simulation. For a power system with high-penetration wind power, various methods are proposed in existing research to improve the system security by utilizing the battery energy storage systems (BESSs). The BESS-based methods can be typically classified as the wind power smoothing method and fast frequency response method. Therefore, this report aims to evaluate the effectiveness of typical BESS-based methods in mitigating wind power fluctuations and providing fast frequency response. To achieve these objectives, simulation studies were conducted using a modified Kundur's 2-area 4-generator test system. The simulation results indicate that incorporating BESSs can effectively mitigate wind power fluctuations and improve power system frequency quality.